Differences in sister-chromatid exchange frequency between homologous chromosomes in Muntiacus muntjak - Rachel A.J.; Sharma T.; Menon V.V. (My University, 2025)
The frequency of sister-chromatid exchanges (SCEs) on homologous autosomes was studied in the peripheral blood lymphocytes of the Indian muntjac. The homologous autosomes differed from one another with respect to the SCE frequency on them. © 1992.